Applying the Foundational Concepts from Early Intervention to Services Provided to Young Children with Visual Impairments: A Literature Review. (May 2018) - Ely, Mindy S.; Ostrosky, Michaelene M.
Introduction: The foundational concepts of early intervention are: family-centered and relationship-based practices, natural environments, child learning, adult learning, and quality team practices (Pletcher & Younggren, 2013). In this literature review, the authors consider the application of these concepts to services provided to families of infants and toddlers with visual impairments (that is, those with blindness or low vision) by vision professionals. Methods: Three databases (ERIC, ProQuest, and PsychINFO) were used to search for articles from 1997 to 2016, focusing specifically on infants and toddlers with visual impairments. Twenty-seven articles met the criteria for inclusion in the review. Results: Family-centered practices are valued by virtually all researchers in the field of visual impairment. Practices that promote parent-child relationships are especially important, given the specialized needs for early communication and the development of strong social relationships. Concerning the natural environment, commentators from the field of visual impairment are critical of federal definitions of natural environments; however, a broader definition of natural environments is supported. Child and adult learning are viewed as important for the promotion of positive outcomes for children and families who receive early intervention services, as is practice that promotes the formation of quality teams. Discussion: The foundational concepts of early intervention (Pletcher & Younggren, 2013) have applicability to professionals working with infants and toddlers with visual impairments and their families. Research supports these concepts as beneficial in achieving positive child and family outcomes. Implications for practitioners: Pre-service and in-service training programs for visual impairment should include early intervention principles and concepts in a manner that prepares the workforce to address the unique needs of this population.